Glyphosate-resistant Digitaria insularis effect on eucalyptus initial growth - Guidugli, Tauane Botelho [UNESP]; Bacha, Allan Lopes [UNESP]; Martins, Heytor Lemos [UNESP]; Novello, Bruna Dal’Pizol [UNESP]; Alves, Pedro Luis da Costa Aguiar [UNESP] (Springer Nature, 2024)
Eucalyptus are trees sensitive to interference imposed by weeds mainly during the early growth phase. The repetitive use of herbicides with the same mechanism of action has led to the selection of resistant weeds, and Digitaria insularis stands out for its resistance to glyphosate. Due to its occurrence in eucalyptus plantations, knowledge regarding D. insularis interference in eucalyptus early growth is needed to develop management strategies. This study aimed to confirm D. insularis glyphosate-resistence; and also to evaluate the effect of densities and distances of glyphosate-resistant D. insularis, seeded and in regrowth, on the early growth of Eucalyptus urophylla × E. grandis (Clone AEC-144). Prior to eucalyptus’ experiments, D. insularis glyphosate-resistance was confirmed through a dose–response curve experiment. After that, two experiments [one for weed’s first growth (seeded) and other for second growth (regrowth)] were carried out in an open area, in 700 L pots, for 105 days after planting eucalyptus seedlings. The treatments consisted of increasing densities of D. insularis (0, 1, 2 and 3 plants m−2) planted at 10, 20 or 30 cm from the eucalyptus seedlings. Eucalyptus height, stem diameter, leaf area and dry matter were evaluated. The eucalyptus variables most sensitive to interference were leaf and stem dry matter, with reductions of 45% and 88.4%, respectively for weeds seeded and regrowth. Weed second growth (regrowth) interfered more aggressively in eucalyptus growth. The coexistence with D. insularis, regardless of density and distance, negatively interfered early tree growth.
Keywords: Biotic stress; Coexistence; Eucalyptus urophylla × E. grandis; Regrowth; Resources competition; Sourgrass